High incidence of inappropriate alarms in patients with wearable cardioverter-defibrillators: findings from the swiss WCD registry. (14th October 2021) - Kovacs, B; Burri, H; Reek, S; Sticherling, C; Linka, A; Ammann, P; Mueller, A.S; Kobza, R; Haegeli, L; Mayer, K; Eriksson, U; Reichlin, T; et al.
Abstract: Introduction: The wearable cardioverter defibrillator (WCD) uses surface electrodes built into the vest to detect underlying arrhythmia before initiating a treatment sequence. However, it is also prone to inappropriate detection due to artefacts. Purpose: The aim of this study was to assess the alarm burden in patients and its possible impact on clinical outcomes. Methods: The Swiss WCD Registry is a nationwide, retrospective, observational registry. Patients were included from December 2011 until February 2018. Clinical characteristics and data from the WCDs, including alarm burden were analysed. Recordings ≥30 seconds of length were analysed and categorized as VT/VF, atrial fibrillation (AF), supraventricular tachycardia or artefact. Results: A total of 10'653 device alarms were documented in 324 of 456 patients (71.1%) over a mean WCD wear-time of 2.0±1.6 months. Among these, the episode duration was 30 seconds or more in 2996 (28.2%). One hundred and eleven (3.7%) were VT/VF episodes. The remaining recordings were inappropriate arrhythmia detections (2736 (91%) due to artefacts; 117 (3.7%) AF; 48 (1.6%) supraventricular tachycardia). Two-hundred and seven patients (45.0%) had 3 or more alarms per month, whereas 49 patients (10.7%) had 1 or more alarms per day. Body mass index (BMI) was significantly higher in patients with 3 or more alarms per month (p=0.002, 25.6 vs. 27.3 kg/m 2 ) High alarm burden was not associated with a lower average daily wear time (20.8 hours vs 20.7 hours, p=0.785) or a decreased implantable cardioverter defibrillator implantation rate after stopping WCD use (48% vs 47.3%, p=0.156). Conclusions: In patients using WCDs, alarms emitted by the device and impending inappropriate shocks were frequent and most commonly caused by artefacts. A high alarm burden did not lead to a decreased adherence, as determined by average daily wear-times. Obesity was significantly associated with a higher alarm burden. Funding Acknowledgement: Type of funding sources: None.